Haemato-biochemical profile during different stages of lactation in local Sahiwal crossbred dairy cows at Savar area of Dhaka district of Bangladesh (Asian Journal of Medical and Biological Research, 2021)
The present study was carried out to investigate the haemato-biochemical profile during different stages of lactation in local Sahiwal crossbreed dairy cows at Savar area of Dhaka district of Bangladesh. Twenty four local Sahiwal crossbreed cows were selected randomly from different small farms and divided into three groups: early stage lactation (1-3 months), mid stage lactation (4-6 months) and late stage lactation (7-9 months). Blood samples were collected during three stages of lactation. There were no statistical significant (p